Decreased protein C pathway activity in COVID-19 compared to non-COVID sepsis: an observational and comparative cohort study - Rühl, Heiko; Bode, Christian; Becher, Tobias; Eckert, Sebastian; Mohsen, Ghaith; McRae, Hannah L.; Müller, Jens; Reda, Sara; Loßnitzer, Dirk; Oldenburg, Johannes; Putensen, Christian; Pötzsch, Bernd (Biomedicines, 2024)
Sepsis-associated coagulopathy increases risk of mortality. Impairment of the anticoagulant protein C (PC) pathway may contribute to the thrombotic phenotype in coronavirus disease 2019 (COVID-19) sepsis. This study assessed the functionality of this pathway in COVID-19 and non-COVID sepsis by measuring its key enzymes, thrombin and activated PC (APC). The study population included 30 patients with COVID-19, 47 patients with non-COVID sepsis, and 40 healthy controls. In healthy controls, coagulation activation and subsequent APC formation was induced by 15 µg/kg recombinant activated factor VII one hour before blood sampling. APC and thrombin in plasma were measured using oligonucleotide-based enzyme capture assays. The indirect thrombin markers prothrombin-fragment 1+2 (F1+2) and thrombin-antithrombin complex (TAT) were also measured. Compared with stimulated healthy controls, median thrombin, F1+2, and TAT levels were higher in patients with COVID-19 (up to 6-fold, p < 2 × 10−6) and non-COVID sepsis (up to 4.7-fold, p < 0.010). APC levels were 2.4-fold higher in patients with COVID-19 (7.44 pmol/L, p = 0.011) and 3.4-fold higher in non-COVID sepsis patients (10.45 pmol/L, p = 2 × 10−4) than in controls (3.08 pmol/L). Thrombin markers and APC showed correlation in both COVID-19 (r = 0.364-0.661) and non-COVID sepsis patients (r = 0.535-0.711). After adjustment for PC levels, median APC/thrombin, APC/F1+2, and APC/TAT ratios were 2-fold (p = 0.036), 6-fold (p = 3 × 10−7) and 3-fold (p = 8 × 10−4) lower in the COVID-19 group than in the non-COVID sepsis group, and the latter two were also lower in the COVID-19 group than in stimulated healthy controls. In conclusion, it was found that a comparatively lower anticoagulant APC response in COVID-19 patients as compared to non-COVID sepsis patients, potentially linked to endothelial dysfunction, contributes to the prothrombotic phenotype of COVID-19 sepsis.